Delivering a MOOC using a social networking site: The SMOOC design model - Ostashewski, Nathaniel; Reid, D. (IADIS Press, 2012)
This paper articulates a design model for a SMOOC or Social networking site situated MOOC. A noncredit open online course entitled Social Media Tools and Supporting Your Professional Learning (AUSMT) is one example of a SMOOC that the researchers have designed and delivered. The course was delivered within a social networking site (SNS) group and the learning activities utilized social media tools for content delivery and student engagement. A secondary outcome of the course is a persistent “group” repository of resources and activities for students who have access to the specific SNS. The AUSMT course can be characterized as a type of Massive Open Online Courses (MOOC) as it has similar organization and delivery of learner activities/engagement. Developed using the Networked Learning Framework (NLF), this course is an example of an implementation that makes use of a SNS “group” as an organizational structure and virtual meeting place for learners. One challenge identified in the literature with respect to MOOCs is the lack of control that may be needed for pedagogical or organizational reasons. The SMOOC model addresses this challenge and provides other benefits which make the concept useable in more formalized learning. Additional research detailing the specific student activities and resources resulting in student learning in a SMOOC, as well as how these can be assessed for more formalized learning are topics identified for future research.